Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the simultaneous equations step-by-step:
1. Equations Given:
[tex]\[ \begin{array}{l} 2x + 3y = 13 \quad \cdots (1) \\ 4x - y = -2 \quad \cdots (2) \end{array} \][/tex]
2. Express one variable in terms of the other using Equation (2):
[tex]\[ 4x - y = -2 \implies y = 4x + 2 \quad \cdots (3) \][/tex]
3. Substitute the expression for [tex]\( y \)[/tex] from Equation (3) into Equation (1):
[tex]\[ 2x + 3(4x + 2) = 13 \][/tex]
[tex]\[ 2x + 12x + 6 = 13 \][/tex]
[tex]\[ 14x + 6 = 13 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 14x = 13 - 6 \][/tex]
[tex]\[ 14x = 7 \][/tex]
[tex]\[ x = \frac{7}{14} \][/tex]
[tex]\[ x = \frac{1}{2} \][/tex]
5. Substitute [tex]\( x = \frac{1}{2} \)[/tex] back into Equation (3) to find [tex]\( y \)[/tex]:
[tex]\[ y = 4 \left( \frac{1}{2} \right) + 2 \][/tex]
[tex]\[ y = 2 + 2 \][/tex]
[tex]\[ y = 4 \][/tex]
6. Solution:
[tex]\[ \boxed{x = \frac{1}{2}, \, y = 4} \][/tex]
Thus, the solution to the simultaneous equations is [tex]\( x = \frac{1}{2} \)[/tex] and [tex]\( y = 4 \)[/tex].
1. Equations Given:
[tex]\[ \begin{array}{l} 2x + 3y = 13 \quad \cdots (1) \\ 4x - y = -2 \quad \cdots (2) \end{array} \][/tex]
2. Express one variable in terms of the other using Equation (2):
[tex]\[ 4x - y = -2 \implies y = 4x + 2 \quad \cdots (3) \][/tex]
3. Substitute the expression for [tex]\( y \)[/tex] from Equation (3) into Equation (1):
[tex]\[ 2x + 3(4x + 2) = 13 \][/tex]
[tex]\[ 2x + 12x + 6 = 13 \][/tex]
[tex]\[ 14x + 6 = 13 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 14x = 13 - 6 \][/tex]
[tex]\[ 14x = 7 \][/tex]
[tex]\[ x = \frac{7}{14} \][/tex]
[tex]\[ x = \frac{1}{2} \][/tex]
5. Substitute [tex]\( x = \frac{1}{2} \)[/tex] back into Equation (3) to find [tex]\( y \)[/tex]:
[tex]\[ y = 4 \left( \frac{1}{2} \right) + 2 \][/tex]
[tex]\[ y = 2 + 2 \][/tex]
[tex]\[ y = 4 \][/tex]
6. Solution:
[tex]\[ \boxed{x = \frac{1}{2}, \, y = 4} \][/tex]
Thus, the solution to the simultaneous equations is [tex]\( x = \frac{1}{2} \)[/tex] and [tex]\( y = 4 \)[/tex].
Answer:
x = 0.5
y = 4
Step-by-step explanation:
Given:
- 2x + 3y = 13 (Equation 1)
- 4x - y = -2 (Equation 2)
Firstly, make y the subject of the formula in equation 2 for simplicity.
Note: you can still use Equation 1 if you want to do so.
4x - y = -2
4x - y + 2 = -2 + 2
4x + 2 - y + y = y
y = 4x + 2 (Let's call that Equation 3)
Next step, Substituting equation 3 to equation 1
What is substitution?
Substitution in simutaneous equations is the process of inserting values of variables into other equations.
For example, x = 3 and y = 2x then y = 2 * 3 = 6
2x + 3y = 13
Where:
- y = 4x + 2
2x + 3(4x + 2) = 13
2x + 12x + 6 = 13
14x = 13 - 6
14x = 7
x = 7/14 = 1/2 = 0.5
The value of x simplifies to 0.5 or [tex]\frac{1}{2} \text{ in fraction}[/tex]
Using the value of x we can plot it into Equation 2
4x - y = -2
4(0.5) - y = -2
2 - y = -2
2 + 2 = y
y = 4
In summary, the solution of the simultaneous equations in (x, y) format results in (1/2, 4)
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.